Avaliação das características de bio-óleo e biochar produzidos por pirólise a partir de biomassas lignocelulósicas - Diehl, Lisiane de Oliveira (2023)
Lignocellulosic biomass is considered one of the alternative renewable resources with the potential to supply the high world energy demand, by reducing dependence on fossil fuels. The use of this valuable resource as raw material to produce biofuels requires transformations through biological, mechanical or thermal processes, such as pyrolysis. Beyond that, an evaluation of physicochemical properties and composition of the products from these processes is necessary to ensure quality to apply as biofuels or others. In this study, residues of pine wood and sugarcane straw were investigated and submitted to slow and fast pyrolysis processes at temperature range of 400 to 600 °C to characterize the solid (biochar) and liquid (bio-oil) products. Comparing the processes for each biomass, pine wood produced a smaller amount of non-condensable gases. For bio-oil yield, significant differences were associated with changes in the pyrolysis parameters. Similar biochar yield was obtained at 400 °C using both biomasses. Yield of the liquid phase and the high heating value of the solid phase increased by increasing heating rate and temperature. The physicochemical properties and composition of the biomass, biochar and bio-oil were analyzed using different methods. For biomasses and biochar, moisture, ash, volatile matter and fixed carbon were evaluated, revealing notable variation. Water content and acid value, were determined by using standard methods and significant changes were observed with the alteration of the pyrolysis parameters and for each type of biomass. The determination of N for biomass and biochar and Cl for biochar was performed by using an elemental analyzer. Also, the concentration of metals, S and P in biomass, biochar and bio-oil an Cl in biomass was evaluated by inductively coupled plasma optical emission spectrometry (ICP-OES). Calcium and K were the major elements for biomasses and biochar and S was the major element for bio-oils. Finally, in a study of the potential adsorbent of biochar, the adsorption capacity of organic dye (methyl red) was observed. The results referring to the pyrolysis processes, physicochemical and compositional analyses showed significant differences related to the biomass type and the pyrolysis conditions and statistical analysis was a useful tool in order to ensure a reliable comparison. The results in this work constitute a set of information useful to the Oil, Gas, Biofuels and Energy Sector and are aligned with the 2030 Agenda of the United Nations, Sustainable Development Goals (SDGs), SDGs 7: Affordable and clean energy, SDGs 9: Industry, innovation and infrastructure and SDGs 13: Climate action.